Coffee agribusiness development strategy in North Benteng Alla Village, South Sulawesi. Issue 1 (October 2020) - Tenriawaru, A N; Hadman, A B; Summase, I; Fudjaja, L; Amiruddin, A
Abstract: The purpose of this study is formulate a coffee agribusiness development strategy in Benteng Alla Utara Village, Baroko District, Enrekang Regency. The analysis used in this study was descriptive qualitative data analysis aimed at explaining the condition of coffee agribusiness, income analysis aims to determine the income level of coffee farmers in Benteng Alla Utara Village, SWOT analysis is used to determine the alternatives that can be done by coffee agribusiness players, especially in the on-farm subsystem and design the right strategy for coffee agribusiness development in Benteng Alla Village, North Baroko District, Enrekang Regency. The results of this study indicate that the coffee agribusiness conditions in Benteng Alla utara village have links between each subsystem. So it needs to be developed again. The strategy that must be done is to increase coffee production by optimizing various existing resources, so that farmers can increase their income. eveloping the market and share of the coffee market, including farmers in coffee agribusiness training activities in order to add insight to farmers to develop their coffee farming. And carry out intensive rejuvenation and maintenance a ctivities of coffee plants and the use of technology that is good for farming and post-harvest processes.